2022
DOI: 10.3390/antibiotics11020179
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Antibiotic Usage Guidelines, Developed and Disseminated through Internet, on the Knowledge, Attitude and Prescribing Habits of Orthokeratology Contact Lens Practitioners in China

Abstract: It has been previously reported that the improper prescribing of antibiotic eye drops is common among orthokeratology (ortho-k) practitioners. Guidelines have since been developed and disseminated to improve their understanding and implementation of antibiotic prescriptions. This study aimed to investigate the influence of these guidelines on the knowledge, attitude, and prescribing habits of ortho-k practitioners by means of a questionnaire, which was administered nationwide via an official online account to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…These lenses are worn during sleep, which may increase the risk of ocular infection. A study by Chen et al [ 5 ] found that guidelines for the best use of antibiotics during contact lens wear significantly improved prescribing habits, which, in turn, affected the compliance of patients with orthokeratology. Bacteria can respond to antibiotics in several ways, including activating their stress response processes.…”
mentioning
confidence: 99%
“…These lenses are worn during sleep, which may increase the risk of ocular infection. A study by Chen et al [ 5 ] found that guidelines for the best use of antibiotics during contact lens wear significantly improved prescribing habits, which, in turn, affected the compliance of patients with orthokeratology. Bacteria can respond to antibiotics in several ways, including activating their stress response processes.…”
mentioning
confidence: 99%